Behavioural interactions between the endangered native fish Saramugo, Anaecypris hispanica, and the invasive bleak, Alburnus alburnus - da Silva, Janine (2020)
Invasive species have the potential to impact native fish through interference competition, which is especially concerning for the conservation of the valuable endemic ichtyofauna of the Iberian Peninsula. This study investigated the potential negative effect of the invasive bleak Alburnus alburnus on the behaviour of the critically endangered Iberian saramugo Anaecypris hispanica. The behaviour patterns were analysed under experimental conditions in outdoor tanks through observations on shelter use, shoaling, space use, swimming and direct interactions between individuals. Saramugo showed a strong social character, being the monospecific shoal a sharp behavioural feature, independently on the presence of the bleak. Sheltering was also an important and consistent behaviour to the species. The presence of the bleak resulted in the increase of individual space exploration, as well as swimming and especially fast swimming events, and a wider use of the available space, including the water column in addition to the bottom. This points to higher activity levels of saramugo in the presence of the bleak. Negative direct interactions, particularly through aggression, were not frequent but only occurred when the bleak was present and were always triggered by this species. The future possible coexistence of these two species in the wild is likely to promote an increase of saramugo individual’s activity, reducing shelter use and leading to higher metabolic expenses as well as predation risk.